2014
DOI: 10.1161/strokeaha.114.006293
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Access to Acute Stroke Care in the United States

Abstract: Background and Purpose-Only 3% to 5% of patients with acute ischemic stroke receive intravenous recombinant tissuetype plasminogen activator (r-tPA) and <1% receive endovascular therapy. We describe access of the US population to all facilities that actually provide intravenous r-tPA or endovascular therapy for acute ischemic stroke. Methods-We used US demographic data and intravenous r-tPA and endovascular therapy rates in the 2011 US Medicare Provider and Analysis Review data set. We estimated ambulance resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
141
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 27 publications
(25 reference statements)
1
141
1
1
Order By: Relevance
“…In a study of the 2011 US population, only 0.5% of AIS patients underwent EVT, and 56% of them were 60-minute drive away to an endovascular-capable hospital. 7 Health systems need organizational changes to assure that patients who are candidates for EVT can have access to timely adequate care. In Catalonia, a decentralized stroke care model was progressively developed from 2006 to 2013 to ensure rapid access to IV r-tPA, which currently reaches 15% of AIS patients throughout the region.…”
Section: Pérez De La Ossa Et Al Population Endovascular Therapy Rate mentioning
confidence: 99%
“…In a study of the 2011 US population, only 0.5% of AIS patients underwent EVT, and 56% of them were 60-minute drive away to an endovascular-capable hospital. 7 Health systems need organizational changes to assure that patients who are candidates for EVT can have access to timely adequate care. In Catalonia, a decentralized stroke care model was progressively developed from 2006 to 2013 to ensure rapid access to IV r-tPA, which currently reaches 15% of AIS patients throughout the region.…”
Section: Pérez De La Ossa Et Al Population Endovascular Therapy Rate mentioning
confidence: 99%
“…In a study of the US population, Adeoye et al reported that 19% reside more than 60 minutes from IV-tPA capable centers, half more than 60 minutes from endovascular-capable centers by ground transport, and 15% more than 60 minutes from endovascular-capable centers by air transport (assuming its availability). 1 In just over 2 decades, advancement in catheter-based endovascular technologies has revolutionized AIS care. These catheter technologies inspired a completely new paradigm for the treatment of AIS.…”
mentioning
confidence: 99%
“…rt‐PA has been shown to improve outcomes of survival and independence 7, 8, 12, 13, 14, 15. However, its use is limited by the very short window of opportunity for treatment and risk of bleeding, making less than 6% of stroke patients eligible for such treatment 16, 17. In a pooled analysis, the NNT for achieving an mRS score of 0 to 1 was 4.5 for OTT of <90 minutes, 9 for OTT 91 to 180 minutes, and 14 for OTT 181 to 270 minutes 8.…”
Section: Discussionmentioning
confidence: 99%